The EBITDA disclosed by companies listed on Brazil stock exchange (B3): locations, types, and occurrence count - Kistner, Shaiane Pisa; Platt Neto, Orion Augusto (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To identify the types of EBITDA and locations disclosed by publicly traded companies in Brazil. Methodology: The study is documental, with data from the annual reports of Brazilian listed companies, using statistical techniques of univariate descriptive analysis. Results: 87.7% of the sample (336 companies) disclosed some form of EBITDA. Of these, 94.3% (317 companies) disclosed the Original EBITDA with conciliation, as regulated by the Brazilian Securities and Exchange Commission (CVM). However, 12 companies (3.1% of the sample) only disclosed Adjusted EBITDA (without publishing the Original EBITDA in parallel), not in accordance with the regulation. The reports with the highest frequency of EBITDA disclosure were: the Reference Form (RF), with 80%; the Management Report (MR), with 63%; and the Notes to Financial Statements (NFT), with 6%. As for the variables Number of Occurrences of the Term EBITDA (NOTE), it was observed that: the RF was the report with the highest frequency, with 73% of mentions; 37 companies (9.7% of the sample) did not mention EBITDA in any of the three reports analyzed (NOTE Total = 0); and the median and average of NOTE Total were 57.0 and 66.7 occurrences, respectively, among non-zero. Contributions of the Study: There is a certain variability on the part of the entities regarding the ways and places of disclosing information of an optional nature, such as EBITDA. In this sense, attention to voluntary disclosures is opportune, since it includes risks of disclosures that diverge from business reality. There has been few research into such disclosures in Brazil. For the capital markets, it is relevant to know how EBITDA is being disclosed by entities, given the risks of user manipulation and non-compliance with the standards.